Characterization of breast tissues combining x-ray fluorescence and scattering spectroscopy: A Monte Carlo computational study. (February 2019) - Antoniassi, M.; Maciel, K.F.R.; Manfre, F.A.; Fagundes, A.C.F.; Conceição, A.L.C.
Abstract: The study of spectroscopic techniques that allow obtaining information about breast tissues can be useful for understanding the relationship between tissue composition and the carcinogenic process. In addition, the study of these techniques can serve as a basis for the development of new imaging techniques to complement the diagnosis of breast cancer. Therefore, the objective of the present work is to study by Monte Carlo computational simulation the possibility of mapping breast tissues samples, combining x-ray fluorescence and scattering techniques, exploring the complementarity and ability of these techniques for obtaining morphological and chemical information of the samples. Fluorescence spectra obtained by the simulations were used for mapping the spatial distributions of trace elements (Ca, Fe Cu, Zn) in the simulated sample. In addition, the scattering spectra were used to produce images based on Rayleigh to Compton scattering ratio ( R/C ) and on the full width at half maximum ( FWHM ) of the Compton scattering spectrum. The results showed that the fluorescence and scattering techniques are complementary and can produce images that allow distinguishing between the various breast tissues regions inside the sample. Fluorescence technique showed to be sensitive to the typical concentrations of the investigated trace elements while the R/C and FWHM techniques allowed mapping spatial information related to the effective atomic number, being particularly sensitive to differences of oxygen and carbon percentage of the tissues. Finally, the results showed that as higher the incident energy as higher the contrast of the R/C and FWHM scattering images. When compared to conventional transmission images, R/C images presented better contrast for incident energies above ≈ 23 keV while FWHM images presented lower contrast for all the investigated energy range. Highlights: A Monte Carlo computational simulation combining x-ray fluorescence and scattering techniques was implemented. Fluorescence and scattering techniques produce images that allow mapping sample of breast tissues. Fluorescence and scattering techniques are complementary for breast tissue characterization.